PENGARUH DOSIS LARUTAN KAPUR DAN TAWAS DALAM MENURUNKAN PHOSPAT (PO4 ) PADA LIMBAH CAIR DI RSUD Dr. M. ASHARI KABUPATEN PEMALANG - Triningsih Triningsih; Khomsatun Khomsatun; Hari Rudijanto IW (Poltekkes Kemenkes Semarang, 2021)
Background of wastewater generated by various activities in the hospital environment after going through the process of treatment at the Environmental Health Installation the result of phosphate parameters which is 4.88 mg / l exceeds the quality standard of Central Java Regulation No. 5 of 2012 which is 2 mg / l, so that it has the potential to pollute the environment if the parameters contained therein exceed the specified quality standards. Liquid wastes containing phosphates and cause environmental problems in the form of eutrophication, namely water pollution caused by the large amount of nutrients in the aquatic ecosystem. The research objective is to determine the Effect of Lime and Alum Dose Solution in Reducing Phosphate in Liquid Waste in RSUD dr. M. Ashari Pemalang Year 2020. The sample used 36 samples. The research method used is quasi-experimental research. The research design used in this study is the pretest and post-test design before treatment and after treatment with different doses of lime solution and alum solution, with the Paired sample T test. The results at pH have an effect after the addition of lime solution and alum pH rises so that it is alkaline in wastewater, for phosphate after adding a dose of lime solution 26.37 gr / l and alum 26.85 gr / l, 14.55 gr / l and alum 17.46 gr / l there is an influence on the decrease in phosphate by value 0,000 mg / l (P 0.05) for addition of 10 gr / l lime solution and 10 gr alum / alum with a value of 0.007 mg / l (P 0.05). Conclusions are all significant but researchers prefer the 10 gr / l lime and 10 gr / l alum because of the effect on the sediment is slight, the pH is not basic and the temperature also has no effect.